Agreement between the Carter Center and Institute of Governance Studies on Granting - The Carter Centre; Institute of Governance Studies, BRAC University (Carter Center and BRAC University, 2013)
1. Recipient. 2. Grant period. 3. Grant amount. 4. Purpose- a. Engage in the following activities. and b. Provide the following deliverable. 5. Plan and budget. 6. Payment Schedule. 7. Accounting and audit. 8. publication. 9. Additional funding and refund of unspent funds. 10. Termination of agreement. 11. Acceptance.